E-044 The Penumbra 5MAX, 4MAX and 3MAX Reperfusion Catheters in Treatment of Acute Ischaemic Stroke: Initial Clinical Experience. (14th July 2013) - Farkas, J; Arcot, K; Walzman, D; Kumar, R; Delbrune, J; Papamitsakis, N; Margulis, Y; Dash, S; Levin, K; Azhar, S
Abstract : Introduction/Purpose: The new material composition and larger, tapered lumen in the distal end of the novel Penumbra MAX System reperfusion catheters are designed to enhance aspiration efficiency with improved trackability. Reported herein are results from a retrospective multicentre study with the Penumbra System 5MAX, 4MAX and 3MAX reperfusion catheters in the treatment of acute ischaemic stroke secondary to large vessel occlusion. Materials and Methods: A retrospective case-review of 19 consecutive acute ischaemic stroke cases treated with the Penumbra System either as a standalone device or in combination: 5MAX (n=8), 4MAX (n=6) and 3MAX (n=8), from July 2012 through December 2012 was undertaken. Clinical experience at 3 institutions was collected and reported in the first six months after device release. Occlusions were located in the MCA M1and M2 (n=11), ICA and ICA/MCA (n=6), and vertebrobasilar arteries (n=2). Results: Eighteen of 19 cases (94.7%) were successfully recanalised to TICI 2 and 3 using the Penumbra MAX System. Complete revascularisation to TICI 3 was achieved in 16 of 19 (84%). The mean patient age was 70.3 ± 13.9 years; the median NIHSS score at presentation was 19 (15 to 29). All patients presented with TICI scores of 0 or 1. At discharge, the median NIHSS score was 14 (1 to 29). One death due to cardiac arrest occurred at 15 days post-procedure. In one patient, stroke in a new territory was observed and treated with IA rtPA. One ICH was found in a previously unaffected region, possibly secondary to IV rtPA therapy. Conclusion: Early multicentre experience indicates that the 5MAX, 4MAX and 3MAX reperfusion catheters have enhanced aspiration efficiency and trackability. Follow-up studies will be required to verify these findings. Disclosures: J. Farkas: None. K. Arcot: None. D. Walzman: None. R. Kumar: None. J. Delbrune: None. N. Papamitsakis: None. Y. Margulis: None. S. Dash: None. K. Levin: None. S. Azhar: None.